Correlation between Different Helicobacter Morphotypes and Histological Changes in Pig Gastric Mucosa - Pejčinovska, Nataša; Lalošević, Dušan; Lalošević, Vesna; Čapo, Ivan; Potkonjak, Aleksandar (Acta Scientiae Veterinariae, 2018)
Background: Two distinct morphologic types of bacteria which belong to the Helicobacter species, have been described in pigs: once or twice curved Helicobacter pylori-like bacteria (HLO) and the multicoiled, Gastrospirillum-like bacteria (GLO). The objective of this study was to determine the incidence of Helicobacter spp. using modified Giemsa stain and to define the relationship between presence of Helicobacter spp. and histopathological changes of gastric mucosa in pigs. Materials, Methods & Results: A total of 120 pig stomachs (60 from intensive and 60 from extensive breeding) were enrolled in this study and 240 fragments of fundic and pyloric mucosa were taken for histopathological examination. By modified Giemsa staining of gastric mucosa, Helicobacter-like organisms were confirmed in 4/60 (6.67%) of pigs in intensive and 5/60 (8.33%) of pigs in extensive breeding. The incidence of tightly spiral shaped Gastrospirillum-like organisms in pigs of intensive and extensive breeding were 5/60 (8.33%) and 9/60 (15%), respectively. The severity of gastritis was scored to the Sydney System with some modifications. There was no significant difference between HLO-positive and HLO-negative fundic mucosa in pigs of both breeding systems. In contrary, there was significant difference between HLO-positive and HLO-negative pyloric mucosa of pigs in intensive (P < 0.001) and in extensive breeding (P < 0.05). In intensive breeding, there was significant difference between GLO-positive and GLO-negative fundic mucosa (P < 0.05), while there was no significant difference between GLO-positive and GLO-negative pyloric mucosa. Discussion: The prevalence of Helicobacter spp. bacteria were in coherence with literature data. The higher prevalence of both morfological type of bacteria, were considered in pigs in extensive breeding. the hygienic conditions and managment factors in pigs farm are the possible impact for higher bacterial transmission. The association of high prevalence of H. pylori and poor hygienic condition was shown by epidemiological studies conducted on humans. In both, humans and pigs, the presence of H. pylori correlates with an inflammatory response, but there are differences in inflammatory cell population. In H. pylori infected humans, neutrophils composed the bulk of cellular infiltrate, while in pigs, the primary inflammatory cell was the lymphocyte, which is in accordance to results published by others autors. Thus it indicates that different hosts exhibit a different pathohistological response to the Helicobacter spp. infection. In human as well as in veterinary pathology, the fact of the different pathogenicity of various Helicobacter species is well known. In all HLO-positive pyloric mucosa, moderate to severe focal or diffuse infiltration of mononuclear cells and lymphoid follicles with germinal centers, were observed. A similar conclusion was drawn from results of an experimental infection study in pigs. There was signifficance between HLO-positive and HLO-negative pyloric mucosa in both, intensive and extensive breeding. In the contrast, GLO were not associated with the presence of severe gastritis, but only with mild to moderate superficial infiltration of lymphocytes and plasma cells in both, fundic and pyloric mucosa. There was no significant difference between GLO-positive and GLO-negative pyloric mucosa of pigs in both breeding systems. Despite the low gastritis score of fundic mucosa in pigs in intensive breeding, there was a significance difference between in GLO-positive and GLO-negative fundic mucosa. It is believed that the possible reason of such results is the meals with low fiber content and low particles size. These results suggest that the presence of HLO, but not of GLO is associated with the pyloric gastritis in pigs.